1999
DOI: 10.1159/000055522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical and Digital Assessment of Nuclear Optical Density

Abstract: To compare the standardised Nidek EAS-1000 densitometric analysis of the lens with clinical assessment of the nucleus at an early stage of cataract development, 1,200 eyes of 1,204 participants of the VECAT study were assessed at the baseline using both subjective and objective lens grading. Standardisation of the automatic slit image analysis was achieved using a custom-designed EAS-1000 Software version 3.01c. Among 6 measurements of nuclear optical density, the mean pixel luminescence of integrated anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Although photographic image analysis densitometry, [14][15][16][17] or digital image analysis [18][19][20] as it becomes more widespread, might provide some more objective measures to enhance our preoperative assessment of cataracts and facilitate studies on progression of lens opacities, 21 the LOCSIII and other cataract grading systems have been shown to have high inter-observer and intra-observer repeatability 13,18,[22][23][24] and to demonstrate some consistency between different classifications. [24][25][26][27] New techniques such as photon spectroscopy for in vivo analysis of lenses remain to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although photographic image analysis densitometry, [14][15][16][17] or digital image analysis [18][19][20] as it becomes more widespread, might provide some more objective measures to enhance our preoperative assessment of cataracts and facilitate studies on progression of lens opacities, 21 the LOCSIII and other cataract grading systems have been shown to have high inter-observer and intra-observer repeatability 13,18,[22][23][24] and to demonstrate some consistency between different classifications. [24][25][26][27] New techniques such as photon spectroscopy for in vivo analysis of lenses remain to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing Scheimpflug and retroillumination digital photography with computerised analysis of lens opacities has allowed progression of cataract to be measured with great precision. [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] This method, cost effective for the large epidemiological studies, 89 is probably the best technique for recording cataract changes.…”
Section: Quantification Of Lens Opacity Measurements In Risk Factor Amentioning
confidence: 99%
“…Robmann et al [10] reported that the cataract density measured by EAS-1000 was significantly correlated with clinical assessment of the nuclear density and therefore its value was used in this study. On the other hand, it is actually difficult to measure the true AL and thus directly evaluate the effect of cataract density on the AL measurement.…”
Section: Introductionmentioning
confidence: 99%